2020
DOI: 10.2298/tsci200317194n
|View full text |Cite
|
Sign up to set email alerts
|

Study of vacuum and freeze drying of bee honey

Abstract: The aim of this research is to study the drying kinetics of vacuum-dried and freeze-dried bee honey produced from two different varieties: Sunflower honey (Helianthus Annuus L.) and Acacia honey (Robinia pseudo acacia L.). Vacuum drying treatments were carried out with the honey samples? initial temperatures of +25?C, -20?C and -40?C. Water content, total soluble solids, as well as the water activity of fresh and dried honey samples were determined. Freeze-drying of bee honey with initial sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…The diastase enzyme is found naturally in honey [ 68 ]. The diastatic activity of honey is correlated with the source of nectar and with the geographical origin of honey [ 59 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diastase enzyme is found naturally in honey [ 68 ]. The diastatic activity of honey is correlated with the source of nectar and with the geographical origin of honey [ 59 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have concluded that HMF can be present in low concentrations in natural honey, being an indicator of its freshness. The concentration of HMF depends on other parameters of honey, such as light exposure, pH, acidity, water content [ 68 , 80 ]. According to the European legislation and the Codex Alimentarius, the concentration of HMF allowed in honey can vary up to 40 mg/kg (80 mg/kg in tropical honey) [ 1 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spray drying process is a widely used method for producing powder products such as pharmaceuticals, powdered foods, dairy products, detergents and chemicals [1,2]. It minimizes the thermal damage to liquid samples as it provides a shorter exposure (5-100 s) to heat during the drying process, and thus protects qualities of the end-products, such as the color and taste [3,4,5]. Moreover, spray drying process, because of low operating costs, is regarded as the most economic drying technique [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Various adsorbents with different adsorption capacity such as silica gels, zeolites, composites, activated carbon, metal organic frameworks, or even dry coconut coir and durian peels can be used for air dehumidification [12]. In industrial dehydrators, however, water evaporation is carried out with the use of vacuum [11,13,14]. Vacuum drying involves the evaporation of water under low pressure conditions where the boiling temperature of the water inside the substance dried product is approx.…”
Section: Introductionmentioning
confidence: 99%
“…This type of honey dehumidification is particularly desired for its speed and preserving the enzymes activity in honey due to low-temperature treatment [13]. There are also hybrid solutions, such as vacuum freeze drying [14,15] in which water removal from honey is carried out by sublimation of ice from the dried substance under low pressure (below 611.2 Pa) and temperature (e.g., in the range −40; −25 • C).…”
Section: Introductionmentioning
confidence: 99%